Equipment Investment and Economic Growth - Long, J. Bradford De; Summers, Lawrence H. (Quarterly Journal of Economics, 1991)
Using data from the United Nations Comparison Project and the Penn World Table, we find that machinery and equipment investment has a strong association with growth: over 1960–1985 each extra percent of GDP invested in equipment is associated with an increase in GDP growth of one third of a percentage point per year. This is a much stronger association than found between growth and any of the other components of investment. A variety of considerations suggest that this association is causal, that higher equipment investment drives faster growth, and that the social return to equipment investment in well-functioning market economies is on the order of 30 percent per year.